Conceptual Framework of Islamic Education in the Digital Era: Challenges, Opportunities and Strategies - Syafaruddin, Baso (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The development of the digital era has brought significant changes in various aspects of life, including in the Islamic education system. This paper examines the transformation of technology in Islamic education, the challenges faced, and the opportunities that can be utilized to improve the quality of Islamic education in the digital era. This study employs a literature-based methodology. Data collection was carried out from various literature in the form of scientific articles, books, and various other sources. In the midst of the unstoppable flow of globalization and the digital revolution, the world of Islamic education faces unprecedented challenges and opportunities. Technological transformation has fundamentally changed the way we learn, teach, and understand religious knowledge. This change not only touches on the technical aspects of learning but also presents a new paradigm in transmitting Islamic values to the digital generation. This study suggests several strategies for navigating the digital era, including implementing system changes in Islamic educational institutions to facilitate digital transformation. In addition to core competencies, educators must also possess supporting qualifications and competencies, such as agility, innovation, creativity, anticipation, experimentation, open-mindedness, and networking skills. This allows Islamic educational institutions in the digital age to be managed according to everyone's expectations.